Coronavirus Disease (COVID-19): Reviews, Applications, and Current Status - Tanweer Alam; Shamimul Qamar (Jurnal Informatika Universitas Pamulang, 2020)
Presently, the COVID‐19 has directly affected the lives of millions of people. COVID-19 disease symptoms are involving fever, malaise, chest infection, and breathing difficulties, were recognized. The existence of these symptoms is continuously becoming recognized. World Health Organization (WHO) had mentioned the wide diagnostics test besides COVID-19 that would also assist medical facilities to recognize infectious diseases as well as currently focusing efficiently on preventing and afterward defeating these kinds of viral diseases. Infections are usually transmitted among human beings in direct contact, greatest through the liquid bubbles generated through speaking coughing or sneezing. Throughout this paper, the authors review the COVID 19 pandemic, its history, current updates, contact tracing applications, and use of emerging technologies like the Internet of Things (IoT) and Blockchain for stopping the spreading. These emerging technologies provide services online to the patient from a long distance in real-time.